Integration of Local and Universal Values in Indonesian Criminal Law Reform: Integrasi Nilai Lokal dan Universal dalam Pembaruan Hukum Pidana Indonesia - Abdul Wahid; Amiruddin Hanafi; Syachdin Syachdin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The reform of Indonesia’s criminal law has culminated in the enactment of Undang-Undang Nomor 1 Tahun 2023, which introduces a new Criminal Code (KUHP) reflective of both domestic values and international principles. Specific Background: Indonesia’s previous criminal legislation, a legacy of Dutch colonial law, often failed to accommodate the nation’s socio-cultural diversity and evolving legal landscape. Knowledge Gap: Despite its significance, limited scholarly analysis has been conducted on how the new KUHP integrates local customary norms with universal legal principles. Aims: This study aims to analyze the integration of local and universal values within the new KUHP and assess their implications for Indonesia’s legal identity and justice system. Results: The findings reveal that the KUHP explicitly accommodates indigenous norms within its judicial framework, enabling more substantive justice. It also strengthens Indonesia’s legal stance globally by upholding universal principles such as legality and territoriality. Novelty: The research highlights the dual harmonization of normative systems—customary and international—in a unified penal code, a distinctive move in contemporary legal reform. Implications: This integration fosters a more inclusive and culturally responsive legal system, reinforcing Indonesia’s sovereign legal identity while aligning with international legal standards. Highlights: Reflects synergy between indigenous norms and international legal standards. Enhances legal relevance to Indonesian cultural context. Strengthens Indonesia’s role in transnational legal frameworks. Keywords: Criminal Law Reform, Indonesian Legal System, Local Values, Universal Principles, KUHP 2023